Comparative Analysis of Neo-Mabims and KHGT Criteria in Determining the Beginning of Rabiul Awal 1447 H (Study: Bandar Lampung) - Anggarini, Nistiyani; Perawironegoro , Djamaluddin (Journal of Advances in Physics Education, 2026)
This study aims to analyze differences in determining the beginning of the month of Rabiulawal 1447 H using Neo-MABIMS criteria and the Single Global Hijri Calendar (KHGT). It applies a descriptive-comparative approach by integrating astronomical data from BMKG and Stellarium simulations conducted at the coordinates of Bandar Lampung. The parameters examined include the conjunction time (ijtima'), crescent altitude, elongation, and the equatorial coordinates of the Moon and the Sun. The results show that the conjunction occurred on August 23, 2025, at 13:06:22 WIB. However, the crescent altitude and elongation observed in Indonesia on that date do not satisfy the Neo-MABIMS criteria, and only meet the required threshold on August 24, 2025. In contrast, the KHGT criteria allow the beginning of the month globally on August 23, 2025, due to meeting visibility conditions in other regions. These findings indicate that differences arise mainly from variations in criteria thresholds and approaches (regional versus global), rather than discrepancies in astronomical data, contributing to a more objective and scientific understanding of Hijri calendar determination.